Nonspanning Total Wrist Arthrodesis with a Low-Profile Locking Plate - Rancy, Schneider K.; Ek, Eugene T.; Paul, Sophia; Hotchkiss, Robert N.; Wolfe, Scott W. (Journal of Wrist Surgery, 2018)
Purpose This study aims to compare the outcomes and complications of our technique for nonspanning total wrist arthrodesis using a locking plate with the standard carpometacarpal spanning technique.Methods A retrospective review of charts was performed to identify patients who underwent total wrist arthrodesis by the senior author (S.W.W.). We compared the outcomes of 15 cases of nonspanning wrist fusion with a 2.4/2.7 mm locking T plate to 11 cases of spanning wrist fusion with a 2.7/3.5 mm locking compression plate. Minimum follow-up was 3 months. Indications for fusion included rheumatoid arthritis, posttraumatic arthritis, Kienböck's disease, primary osteoarthritis, juvenile inflammatory arthropathy, psoriasis, brachial plexopathy, failed hemi or total wrist arthroplasty, failed four-corner fusion, and failed proximal row carpectomy. The primary outcome was fusion. Secondary outcomes included time to union, patient-rated wrist evaluation score, numerical rating scale pain score, grip strength, and complications.Results All the wrists got fused. There were no significant differences in objective and subjective outcomes between cohorts. There were three complications (27%) in the spanning group, including tendon rupture and peri-implant fracture at the third metacarpal. This was compared with three complications (20%) in the nonspanning group, consisting of hardware removal.Discussion We achieved similar fusion rates employing both spanning and nonspanning total wrist arthrodesis techniques, without necessitating carpometacarpal arthrodesis in the latter. Complications associated with our method were comparably less severe than those reported in the literature. We advocate nonspanning arthrodesis as an alternative method for total wrist fusion with a high union rate and minimal risk of complications at the carpometacarpal joint.Level of Evidence Therapeutic level IV.
Keywords: total wrist arthrodesis; nonspanning; spanning; carpometacarpal; complications